Understanding and applying research design - Abbott, Martin, 1949- (Wiley, 2013)
This introductory guide provides a fresh approach to integrating design and statistics in a hands-on fashion that incorporates the power of SPSS (R) software to solve real-world problems. It explores the areas of design and causation--allowing readers to pose, test, and interpret research questions with live data.